MANAGEMENT ANALYSIS OF THE PRINCIPAL IN IMPROVING THE TEACHERS’ WORK AT MAN I TULUNGAGUNG - M. Rum Wahyudi (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
This research with qualitative approach is to describe the meaning of management analysis of the principal in improving the teachers’ work at MAN I Tulungagung, through the focus of the Principal’s Management which consists of 1) Planning, (2) Organising, (3) Actuating, (4) Supervising. The conclusion of this research shows that (1) The planning which is one by the principal of MAN I Tulungagung in improving the teachers’ work is carried out (a) based on vision and mission, (b) professional analysis, job analysis and future oriented. (c) planning is elaborated in strategic planning, (2) The organizing done by the principal of MAN I Tulungagung is explained as follows : (a) determining tasks from each organization implementer, (b) distributing all of work load, (c) merging tasks rationally and efficiently, (d) determining work mechanism, (e) monitoring. (3) Actuating done by the principal of MAN I Tulungagung is as follows : (a) recommending teachers to follow exercises and education, workshops, and seminars, (b) holding the bond of friendship forum, (c) doing a comparative study, (d) making the library more complete, (e) completing education facilities, (f) registering teachers’ certification for teachers, (g) making scientific study. (4) The evaluating that is done is (a) supervising is done objectively and transparently, (b) supervising is based on the appropriate assessment instrument, (c) the assessment is based on the teachers’ attendance in the classrooms. The recommendation of this research is to maintain academic and non-academic achievement that have been obtained because defending the achievement have the same responsibility and struggle as the effort to get the achievement before, and in order to improve the ability and competence in managerial in order that the objective that have been determined can be achieved optimally